Розробка моделі ініціації проектів у формі ланцюга Маркова - Колеснікова, Катерина Вікторівна; Бондар, Василь Іванович; Москалюк, Андрій Юрійович; Яковенко, Володимир Олександрович (НТУ "ХПІ", 2017)
Розроблена модель ініціації проектів, яка відтворює фрагмент загальної схеми взаємодії основних сутностей проекту у фазі ініціації. При цьому ланцюг Маркова є елементом схеми управління, що включає в себе такі елементи тимчасової організаційної структури проекту: проект, команду проекту, замовника та оточення проекту. Показано, що марківська модель взаємодії учасників проектів у фазі їхньої ініціації, з врахуванням ролі ключового учасника проекту – замовника, дозволяє визначати зміни станів систем і формувати рекомендації щодо ініціації проектів.

The model of the initiation of projects which reproduces a fragment of the general scheme of interaction between the main entities in the project initiation phase is created. Determined that the project initiation through communication links between the four main entities: projects team, environment, the project itself and the customer. The result of the initiation of projects in the emerging communications referred to objects in the design phase through consistency requirements of stakeholders and the adoption of the basic concepts of projects, goal-projects, project planning, evaluation requirements of specialization and competence required for the formation of the project team. This Markov chain is part of the control circuit that includes elements such as temporary organizational structure of the project design, project team, customer and environment project. It is shown that the Markov model of interaction between project participants in their initiation phase, taking into account the role of a key player in the project – the customer can determine changes of state and generate recommendations for initiating projects. Results of the study can serve as a basis for creating models of control objects that contain its organizational structure and reflect the parametric properties of the system to obtain information needed for decision making to initiate projects.
The development of a model initiation of project in a form of Markov chain
Keywords: проекти; ініціація; система; взаємодія учасників; ймовірності станів; ланцюг Маркова; модель; projects; initiation; system; interaction of the participants; probability of states; Markov chain; model